HUBUNGAN INTENSITAS PAPARAN MEDIA SOSIAL DENGAN POLA KONSUMSI JUNK FOOD PADA IBU RUMAH TANGGA - Sudrajat, Agus; Lestari, Catur Retno (Indonesian Journal of Nutrition Science and Food, 2024)
Children's eating patterns and nutritional intake are the responsibility of a mother, therefore a mother must have knowledge and skills in processing food for the family. Good nutritional knowledge will apply food consumption patterns and know how to process healthy food in order to fulfill nutritional adequacy. Apart from that, there are social media factors which are known to be very good in developing modern fast food marketing. When consuming junk food, most people do not pay attention to its nutritional content, so over a long period of time it will affect changes in their nutritional status. This study aims to analyze the relationship between the intensity of social media exposure and junk food consumption patterns among housewives. The design of this research is cross sectional with a sample size of 44 respondents. The data collection instrument uses an online questionnaire, namely Google Form which is distributed via social media. The research results showed that there was a relationship between the intensity of social media exposure and junk food consumption patterns among housewives, p=0.012), and there was also a relationship between social media exposure and body mass index among housewives (p=0.003). The tendency to choose eating habits is influenced by what we see. The existence of social media can also make it easier for consumers to see the latest and interesting food so that buyers are interested in buying it. Apart from that, socio-economic conditions and the practicality of providing food and time support teenagers in choosing junk food.